If it's not what You are looking for type in the equation solver your own equation and let us solve it.
t in (-oo:+oo)
6*t+(5/9)*t-5 = 2*t+(7/3)*t-7 // - 2*t+(7/3)*t-7
6*t+(5/9)*t-(2*t)-((7/3)*t)-5+7 = 0
6*t+(5/9)*t-2*t+(-7/3)*t-5+7 = 0
20/9*t+2 = 0 // - 2
20/9*t = -2 // : 20/9
t = -2/20/9
t = -9/10
t = -9/10
| 6x+4(x-3)=13 | | 92x=883.2 | | 2X-6=3X+7 | | x=150+0.85(x) | | w-147.67=144.67 | | 3/5x21=3x | | .3333p+7=12-.6666p | | (2x^2)/(0.8-x^2)=53.3 | | 3/5+3=21x | | z/325=7 | | z/23=6 | | 1/9p=5/6 | | x=200+0.8(x) | | -5(X-4)+8X=6X-2 | | -6y-9=-3(y+9) | | x+65=50+75 | | 10/27=5/9t | | z^23=6 | | 18y-6=8y-70 | | 50+75=x+65 | | 5(X+4)/6=2X-5 | | 0.2x+1-2=0.5 | | x+(.01x)=15000 | | D=7/3(m-76) | | 2x/2-3x-1=0 | | 5x-3/2+6=-11 | | x-(0.01*x)=1500 | | -7-35/8 | | -6+x-8=24 | | x-(0.1*x)=1500 | | x^2-6x+12=8 | | 8(X-8)=7(X-8) |